Nemvaleukin alfa monotherapy in patients with advanced melanoma and renal cell carcinoma: results from the phase 1/2 non-randomized ARTISTRY-1 trial - Xiaomin He; Emiliano Calvo; David F McDermott; Valentina Boni; Olivier Dumas; Arvind Chaudhry; Sang Joon Shin; Seth D Rosen; Philip R Debruyne; Ulka N Vaishampayan (Journal for ImmunoTherapy of Cancer)
Background Despite improved outcomes with immune checkpoint inhibitors (ICIs) and their combinations in advanced solid tumors, a subset of patients remains unresponsive or progresses, highlighting an unmet need for novel treatments with durable benefit. Nemvaleukin alfa (nemvaleukin, ALKS 4230) demonstrated manageable safety and antitumor activity, alone and in combination with pembrolizumab, across heavily pretreated advanced solid tumors in the ARTISTRY-1 study. We report in-depth antitumor activity, safety, pharmacokinetics, and pharmacodynamics of nemvaleukin monotherapy at the recommended phase 2 dose (RP2D) in advanced melanoma and renal cell carcinoma (RCC) cohorts from ARTISTRY-1.Methods ARTISTRY-1 was a three-part (A, B, and C), multicenter, open-label, phase 1/2 study. Adult patients who had received prior treatment, including ICIs, and had advanced melanoma or RCC were enrolled in Part B. Patients received intravenous nemvaleukin once daily on days 1–5 (21-day cycle) at 6 µg/kg/day (RP2D determined from Part A). Primary endpoints for Part B were overall response rate (ORR) and safety. Secondary endpoints included pharmacokinetic and pharmacodynamic measures.Results From July 2016 to March 2023, 74 patients in Part B received nemvaleukin monotherapy (melanoma, n=47; RCC, n=27). ORR in melanoma and RCC cohorts was 9% (95% CI, 2% to 21%; n=4) and 14% (95% CI, 3% to 35%; n=3), respectively; disease control rate was 50% (95% CI, 35% to 65%; n=23) and 50% (95% CI, 28% to 72%, n=11), respectively, with stable disease ≥6 months observed in 3 (7%) and 2 (9%) patients, respectively. The most common nemvaleukin-related treatment-emergent adverse event of grade 3–4 was neutropenia (melanoma, n=27 (57%); RCC, n=9 (33%)). No patients in either cohort experienced grade ≥3 treatment-emergent adverse events (TEAEs) of cytokine release syndrome or infusion-related reaction. There were no reported capillary leak syndrome TEAEs. Pharmacokinetic parameters for extent and duration of nemvaleukin exposure were similar between the two cohorts. Increases in peripheral CD8+ T-cell and natural killer cell populations from baseline were similar between the two cohorts, with minimal changes in regulatory T cells observed.Conclusions Nemvaleukin demonstrated pharmacodynamic proof of mechanism, with single-agent antitumor activity and manageable safety in patients with advanced melanoma and RCC.Trial registration number NCT02799095.